Tranexamic acid suppresses the release of mitochondrial DNA, protects the endothelial monolayer and enhances oxidative phosphorylation. Issue 11 (2nd April 2019) - Prudovsky, Igor; Carter, Damien; Kacer, Doreen; Palmeri, Monica; Soul, Tee; Kumpel, Chloe; Pyburn, Kathleen; Barrett, Karyn; DeMambro, Victoria; Alexandrov, Ilya; Brandina, Irina; Kramer, Robert; et al.
Abstract: Damage‐associated molecular patterns, including mitochondrial DNA (mtDNA) are released during hemorrhage resulting in the development of endotheliopathy. Tranexamic acid (TXA), an antifibrinolytic drug used in hemorrhaging patients, enhances their survival despite the lack of a comprehensive understanding of its cellular mechanisms of action. The present study is aimed to elucidate these mechanisms, with a focus on mitochondria. We found that TXA inhibits the release of endogenous mtDNA from granulocytes and endothelial cells. Furthermore, TXA attenuates the loss of the endothelial monolayer integrity induced by exogenous mtDNA. Using the Seahorse XF technology, it was demonstrated that TXA strongly stimulates mitochondrial respiration. Studies using Mitotracker dye, cells derived from mito‐QC mice, and the ActivSignal IPAD assay, indicate that TXA stimulates biogenesis of mitochondria and inhibits mitophagy. These findings open the potential for improvement of the strategies of TXA applications in trauma patients and the development of more efficient TXA derivatives. Abstract : The antifibrinolytic drug tranexamic acid (TXA) used in hemorrhagic trauma patients exhibits a wide spectrum of beneficial effects. The present study demonstrates that TXA suppresses the release of a damage‐associated molecular pattern, mitochondrial DNA, from granulocytes and endothelial cells and increases the spare respiratory capacity of mitochondria and adenosine triphosphate production.